A PRAÇA COMO MANIFESTAÇÃO CULTURAL: UM OLHAR SOBRE – UNICENTRO CAMPUS IRATI-PR PÓS-GRADUAÇÃO INTERDISCIPLINAR EM ANA BELA DOS SANTOS AS IDENTIDADES NO BAIRRO - Santos, Ana Bela dos (2016)
Abstract: This study aims to investigate the JoãoStanislawzuk square, in Santa Paula district,Ponta Grossa city - PR, that is a place of residence, ownership and experienced by social groups that inhabit the neighborhood. With interfaces: square, identity and neighborhood the research aims to enable a broader analysis of the life and history of the population that inhabits this place. Based on the authors of geography, psychology and anthropology, we understand that this urban space is characterized as a place of experience and where memory and neighborhood identity play a key role in determining the values, objects, and culture that such people will take over. The first part of the work presents the theoretical framework used in the research, as the object of analysis. In the second part we perform a more detailed observation of the characteristics of the field and social groups that occupy the square. Finally, in the third part, as well as proceed to a detailed examination of the functions that performs the square in the neighborhoods, we also present the categorization of identities of social groups that use the space of the square. The relevance of this research sets up the urgency of studies showing the neighborhood culture as a space in constant transformation, allowing the reader to understand this place as an expression of cultural identity and which is characterized as landscape present in existential relations.